Adaptability of Liberalism and Shiite Political Theory in the Thoughts of Allameh Naieni, A Theoretical Framework for the Iranian Constitutional Revolution - Barkhordari, Aref; Metanat, Mohammad Reza (Advances in Social Sciences Research Journal, 2024)
The purpose of writing this article is to analyze and describe the political thought of Allameh Mohammad Hossein Naeini as one of the most important theorists of the Iranian Constitutional Revolution (1284 AH), who tried to reconcile the components of liberalism and classical Shiite political thought to provide a Theoretical basis for the Iranian Constitutional Revolution. In this article, the treatise "Tanbih al-Ulama and Tanzih al-Mulla is, the most important work of Naeini and some other works that have studied her thought, are examined. In Iranian Constitutional Revolution, those who defended the Constitution against supporters of tyranny began to write their treatises, mainly during period of minor tyrann[1]. The most important goal of these thinkers in writing the treatises is to eliminate tyranny, reduce king, s power and rulers in political system of Qajar period and limiting them to the law of parliament and public will on one hand and explaining the concepts and foundations of liberalism and constitutionalism in a way that is compatible with Islamic law on the other hand. In justifying constitutionalism these treatises has referred more to weaknesses and harms of authoritarian system, as well as to poverty and backwardness of Iranian society, and considered constitutionalism to be the only solution to problems.The aim of these dissertations was to demonstrate the efficiencies and capabilities of Constitution in preserving and strengthening the Iranian society. In fact, they are in line with times have sought to implement a religious copy of liberal system and Western constitution in Iranian society. The most important treatise that written in this field is the book of Tanbih al-Allameh and Tanzih al-Mella written by Mohammad Hussein Naeini which we will examine his theories in this article.